The Descriptive Study of the Students Masteri in Song Comprehension of the Eleventh Grade student At MA AL – Imaroh Wongsorejo in the Academic Year 2019/2020 - Ariadi; Abdul Halim; Sutami Dwi Lestari (Prodi Pendidikan Bahasa Inggris, Universitas PGRI Banyuwangi, 2019)
Minister of education recognize the important of English learning to convey ideas out of Indonesia and to absorb external ideas that can be useful for the nation and state. To face it, the curriculum makes English learning as one of the materials in senior high school. Using text in learning process too much makes the students bored and the learning process becomes less interesting. This research was intended to describe the song comprehension of the eleventh grade students at MA Al-IMAROH Wongsorejo in the2019/2020 academic year. The Research design used in this research is descriptive quantitative.The total populations are 54 students. The researcher used one class of the Eleventh grade students at MA AL-IMAROH Wongsorejo in the 2019/2020 academic year by purposive sampling. The number of samples are 28 students from IPA. The data in this research was collected by giving two tests. The tests used in this research are listening test and essay test. This research used quantitative data. The reseacher showed that the average of song comprehension in MA Al Imaroh 68 which are categorized as enough. The vocabulary comprehension and reading comprehension were analyzed statistically in precentage. The precentage of vocabulary comprehension is 75 % and the precentage of reading comprehension is 59%.Based on the result of data analysis of song comprehension, the teacher could know the student’s ability in song comprehensions which is categorized as bad. Because of the students‟ song comprehension which is categorized as bad, the teacher should search the way to optimize the learning media and material. However the song comprehension now becomes one of the materials in curriculum 2013.